Thermal Conductivity of Frozen Sediments Containing Self-Preserved Pore Gas Hydrates at Atmospheric Pressure: An Experimental Study - Evgeny Chuvilin; Boris Bukhanov (Geosciences, 2019)
The paper presents the results of an experimental thermal conductivity study of frozen artificial and natural gas hydrate-bearing sediments at atmospheric pressure (0.1 MPa). Samples of hydrate-saturated sediments are highly stable and suitable for the determination of their physical properties, including thermal conductivity, due to the self-preservation of pore methane hydrate at negative temperatures. It is suggested to measure the thermal conductivity of frozen sediments containing self-preserved pore hydrates by a KD-2 needle probe which causes very little thermal impact on the samples. As shown by the special measurements of reference materials with known thermal conductivities, the values measured with the KD-2 probe are up to 20% underestimated and require the respective correction. Frozen hydrate-bearing sediments differ markedly in thermal conductivity from reference frozen samples of the same composition but free from pore hydrate. The difference depends on the physical properties of the sediments and on changes in their texture and structure associated with the self-preservation effect. Namely, it increases proportionally to the volumetric hydrate content, hydrate saturation, and the percentage of water converted to hydrate. Thermal conductivity is anisotropic in core samples of naturally frozen sediments that enclose visible ice-hydrate lenses and varies with the direction of measurements with respect to the lenses. Thermal conductivity measurements with the suggested method provide a reliable tool for detection of stable and relict gas hydrates in permafrost.